The Effectiveness of the PjBL Model Assisted by Story Maps Media: The Creative Thinking Skills of High School Students - Laeli, Nurul; Wijayanto, Pradika Adi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Students tend to be passive in expressing new ideas or providing opinions that differ from other students when learning disaster mitigation material takes place. In addition, the learning media used are limited, such as textbooks, YouTube videos, and PowerPoints that do not fully support the development of students' creative thinking skills. Therefore, the study was conducted with the aim of determining the effectiveness of the Project Based Learning model assisted by Story Maps media on the creative thinking skills of grade XI students on disaster mitigation material. This study used a pre-experimental quantitative research type. The sample of this study was class XI E2 at Public High School 1 Purbalingga, with a total of 36 students as the experimental class. The average score of the observation sheet was 79.51%, which means that students' creative thinking skills were